Analisis Risiko Kesehatan Lingkungan Pajanan Nitrogen Dioksida (No₂) terhadap Fungsi Paru pada Petugas dan Pedagang di Lingkungan SPBU - Vradonal, Herzi; Sunarsih, Elvi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study examines the health impacts of NO₂ exposure at Ogan Ilir Regency gas stations on lung function in workers and traders. There are two methods used, namely, the Environmental Health Risk Analysis (ARKL) study method with a deterministic approach system, and the Environmental Health Epidemiology (EKL) method with a Cross-Sectional approach system. The analysis of the non-carcinogenic intake rate due to NO₂ exposure showed a value of 0.004 mg/kg/day, and the Risk Quotient (RQ) risk level showed a NO₂ exposure value of 0.12. Statistical tests showed Body Mass Index (BMI), long-term relationships, frequency, duration of exposure, smoking habits, medical history, and history of allergies with a p-value> 0.05. The conclusion of this study shows that there is no significant relationship with impaired lung function. Keywords: Environmental Health Risk Analysis, Lung Function, Nitrogen Dioxide (NO₂), Air Pollution